Knowledge Sharing, Organizational Capabilities, and Innovation Management to Sustain Competitive Advantage: A Qualitative Multi-Case Study - Ghayth Tahat, (Journal of Management Research, 2024)
The importance of new product development (NPD) and innovative capabilities in marketing, innovation, and business strategy has been recognized by management and researchers. Knowledge management and organizational capabilities are also explored and evaluated by researchers and practitioners. However, the current literature shows a lack of connection between NPD, innovative capabilities, integrated shared knowledge, and organizational capabilities. Also, there is limited knowledge on the impact and the contribution of the integrated shared knowledge and the organizational capabilities to the firm's success, performance, and sustainability. This study aims to determine if there is a link between NPD and innovative capabilities and the integrated shared knowledge and the organization's capability and explore how shared knowledge and the organization's capabilities influence and contribute to NPD, innovative capabilities, and innovative management. A qualitative, multi-site case study through one-on-one, in-depth interviews with primary decision-makers from technology and innovative companies in Jordan is employed. The primary research question is, how do shared knowledge and the organizational capabilities that influence NPD and innovative capability contribute to the firm's success, performance, and sustainability? Respondent interviews are imported and analyzed through NVivo qualitative data analytics software. Findings are also determined using NVivo 11 through theme analysis. A key finding is that shared knowledge and the organization's capabilities are linked and critical for NPD's success and innovative capabilities.